The mediating role of memorable tourism experience on tourist behavior: A perspective on organized tours - Mustafa Çevrimkaya; Burhanettin Zengin (Tourism & Management Studies)
This study aims to determine the effect of destination image on the intention to recommend memorable tourism experiences of tourists participating in organized tours. In this context, the relationships between the variables of destination image, memorable tourism experience, tourist satisfaction and intention to recommend were examined in the research process. Quantitative research methods were used in the study. A questionnaire was preferred as the data collection tool. The population of the research consists of individuals living in Türkiye and having previous experience in organized tours. Data were collected from 950 participants using the convenience sampling technique from this universe. It has been revealed that the destination image has a positive effect on tourist satisfaction, memorable tourism experience and intention to recommend. In this context, it can be said that phenomena such as image, satisfaction and experience affect tourists' perceptions of destination image, and this situation increases the probability of destinations being preferred repeatedly. As a result, it can be concluded that factors with high emotional intensity such as memorable tourism experience and tourist satisfaction affect the intention to recommend.